Avaliação dos efeitos da rutina em modelo de doença de Huntington em Caenorhabditis elegans - Cordeiro, Larissa Marafiga (2019)
Huntington's disease (DH) is a progressive and hereditary neurodegenerative disorder predominantly caused by the expansion of a CAG repeat, which encodes polyglutamine (polyQ). This pathology results in loss of neuronal cells, motor alterations, dementia and is currently a disease without cure. The rutin is a flavonoid found in plants such as Passiflora incarnata, buckwheat, some teas and also in apples. It is known to have antioxidant, cytoprotective, anticancer and neuroprotective activities. Thus, we investigated the effect of in vivo rutin chronic exposure on the DH model using transgenic lines of the nematode Caenorhabditis elegans. The C elegans is a small nematode (± 1 mm), easy to handle, short life cycle, easy to grow and fast generation time. The animals were treated from the L1 stage with 15, 30, 60 and 120 μM rutin until adulthood. We evaluated behavioral assays, polyQ aggregation, oxidative damage, neurodegeneration level, lifespan, and investigated the possible role of autophagy and insulin / IGF1 (IIS) signaling pathways in the beneficial effects induced by the rutin. In general, our data demonstrate that routine treatment reduced polyglutamine (polyQ) protein aggregation in muscle, reduced polyQ mediated neuronal death in ASH sensory neurons, and extended lifespan in C. elegans. The possible mechanisms involved in the actions described are: antioxidant activity per se of the extract, activation of protein degradation (autophagy), and insulin / IGF1 (IIS) signaling pathways. These findings demonstrate that chronic exposure to rutin may play a useful role in the prevention of DH and also provide possible avenues to be explored for the search for new therapies against aging-related proteinopathies.